INSTALASI JARINGAN KOMPUTER SEBAGAI PENUNJANG LAYANAN ADMINISTRASI MASYARAKAT DESA KARANGDUREN KAB. MALANG - Yuri Ariyanto; Atiqah Nurul Asri; Yoppy Yunhasnawa; Faiz Ushbah Mubarok; Mungki Astiningrum (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
At the village level, administrative services are the main service and are directly related to the needs of the community. Administrative services can be in the form of issuing certificates, cover letters, letters of recommendation, legalization, and other letters. For administrative services in correspondence, the problems faced by the Karangduren village office regarding the installation of computer networks. Currently, computers that store data and applications for mailing repositories are not yet connected to other computers, resulting in queuing and slow document processing. With these problems, PPM (Pengabdian Pada Masyarakat) activities will be carried out in the form of "Implementation of Computer Network Installation to Support Mailing Repository Applications at the Karangduren Village Office, Kec. Pakisaji, Kab. Malang". Through PPM activities in Karangduren village, Kec. Pakisaji, Kab. Malang is done to help solve problems regarding the installation of computer networks. By installing a computer network at the village office, all computers in the village office can be connected. So with the installation of this computer network, it can improve the service and performance of the Karangduren Village Office in serving the community. The results of this PPM activity will produce a computer network installation design and a basic computer network manual.